Mother tongues: the Opt Out movement's vocal response to patriarchal, neoliberal education reform. Issue 8 (17th November 2018) - Schroeder, Stephanie; Currin, Elizabeth; McCardle, Todd
ABSTRACT: This article explores the widespread and growing public backlash against high-stakes standardised testing in the United States, following the parent-led Opt Out movement's quest to dismantle neoliberal educational policy by coaching children to boycott standardised tests. We analyse how our participants, mothers and female teachers in Opt Out Florida, use Facebook group pages as on-going critical sites of consciousness development where connected learning, knowing, and action occur. We illustrate how our participants, perceiving their children's teachers as muzzled by neoliberal, patriarchal education reform, banded together to collectively attack a corporatised and violent system of American public education. Our focus on the role of mothers, their defence of teachers, and their attack on patriarchal neoliberalism fits within the larger history of the feminisation of the teaching profession and reveals how mothers in the domestic sphere have organised to wrest teaching from neoliberal reformers.